Perancangan Sistem Follow-Up Berbasis Segmentasi Pelanggan Menggunakan Pendekatan CRM pada UMKM Bakery - Azzahra Nurhaliza; Sri Mulyati (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2026)
The development of information technology has encouraged businesses to utilize customer data as a strategic asset to improve customer relationship management. However Hani Cake & Bakery still manages customer data manually, making it difficult to analyze zustomer behavior, identify loyal customers, and conduct targeted follow-up information sistem using a Customer Relationsip Management (CRM) approach for a bakery MSME. The system was developed using the System Development Life Cycle (SDLC) with the Waterfall model. The proposed system provides features for customer data management, customer segmentation, customer follow-up through WhatsApp, promotion management, and transaction reporting. The result of this study is a web-based information system design that supports customer relationship management activities and assists store managers in implementing more targeted marketing strategies. The proposed system is expected to improve customer data management and strengthen customer relationship in bakery MSMEs.